Ovarian cancer - Olazábal, Mario; Blanchard, Oscar; Giampietro, Carlos; Mainetti, José M; Mautone, José A; Méndez Aserito, Hugo; Rearden, Moisés; Rodríguez de Armas, Ramón (Cirugía del Uruguay, 1981)
Ovarían cancer constitutes a process which the General Surgeon frequently comes accross and which requires solution in the best manner possible. Ovarían cancer constitutes a process which the General Surgeon frequently comes accross and which requires solution in the best manner possible.